Pharmacokinetics of indacaterol, glycopyrronium and mometasone furoate following once-daily inhalation as a combination in healthy subjects. (October 2020) - Vaidya, Soniya; Jauernig, Juergen; Ethell, Brian; Abdallah, Nasri; Machineni, Surendra; Drollmann, Anton; Heudi, Olivier; Last, Stefanie; Hahn, Michael; Radhakrishnan, Rajkumar; Ignatenko, Stanislav; Tillmann, Hanns-Christian
Abstract: Indacaterol (IND), is co-formulated with glycopyrronium (GLY), and mometasone furoate (MF) as a once-daily (o.d.) inhaled fixed-dose combination (IND/GLY/MF) delivered via the Breezhaler® device for maintenance treatment of asthma. We evaluated the steady state plasma pharmacokinetics (PK) of IND, GLY and MF following inhalation of IND/GLY/MF or as monotherapies. This was a randomized, open-label, four-way crossover study. Subjects received IND/GLY/MF 150/50/160 μg (high-dose), IND 150 μg, GLY 50 μg or MF 190 μg (in vitro fine particle mass comparable to 160 μg MF in IND/GLY/MF) via the Breezhaler® device, o.d. for 14 days in each period, with a washout of at least 7 days. PK was characterized on Day 14, up to 24 h post-dose. In total, 36 healthy subjects were randomized. For IND, the geometric mean ratios (90% CI) for AUC0-24h, ss and Cmax, ss were 0.922 (0.878, 0.969) and 1.02 (0.967, 1.08), respectively for the IND/GLY/MF versus IND monotherapy comparison. For GLY, the geometric mean ratios (90% CI) for AUC0-24h, ss and Cmax, ss were 0.986 (0.944, 1.03) and 1.21 (1.09, 1.34), respectively for the IND/GLY/MF versus GLY comparison. For MF, the geometric mean ratios (90% CI) for AUC0-24h, ss and Cmax, ss were 1.16 (1.09, 1.24) and 1.17 (1.09, 1.25), respectively for IND/GLY/MF versus MF comparison. Similar systemic exposure was noted for IND/GLY/MF versus monotherapy for all three mono-components, indicating a lack of PK interaction. Multiple inhaled doses of IND, GLY and MF were safe and well tolerated, when administered alone or in combination. There was no clinically relevant pharmacokinetic interaction between IND, GLY and MF when administered as IND/GLY/MF. Highlights: Inhalation of Indacaterol (IND), glycopyrronium (GLY), and mometasone furoate (MF), administered alone or as IND/GLY/MF combination via the Breezhaler® device over 14 days was safe and well tolerated. There was no clinically relevant pharmacokinetic interaction between IND, GLY and MF when administered as IND/GLY/MF.